Factors influencing condom use in a sample of homosexually active men. Issue 5 (October 1990) - Fitzpatrick, R; McLean, J; Dawson, J; Boulton, M; Hart, G
Abstract : A sample of 502 homosexually active men were recruited from genitourinary medicine clinics and non clinic sources and interviewed in relation to their sexual behaviour and factors that might influence their use of condoms. Three hundred and eighty three men (76%) reported penetrative anal sex in the previous year. Ninety four (25%) had not used condoms in penetrative sex. Failure to use condoms was associated with unfavourable attitudes to them, not knowing close friends or partners who had HIV-related health problems, having fewer sexual partners and being in a closed monogamous relationship. On the other hand levels of awareness about the risks of unprotected anal sex and involvement in gay networks and social groups were not predictors of condom use.